Paulus, die Evangelien, und das Urchristentum : Beiträge von und zu Walter Schmithals - Schmithals, Walter. (Arbeiten zur Geschichte des antiken Judentums und des Urchristentums, 2004)
This volume contains the author's 'late harvest' from the fruits of half a century scholarly research in the fields of the New Testament. The essays on Paul oppose the view of history held by the 'Tübingen School' (F.C. Baur), and point out the importance of literary criticism for the theological interpretation of the pauline letters. The essays on the Letter to the Hebrews assign the appropriate historical place within early Christianity to this New Testament book. The essays on the synoptic gospels force the crisis of synoptic form criticism, and give convincing reasons for the alternative solution concerning the origin of the synoptic tradition. Five contributions complete the author's 'Theologiegeschichte des Urchristentums' edited 1994. In the second part various prominent German New Testament scholars engage into a discussion with Schmithals's contributions.